According to Springer's Encyclopedia of Math entry on differential inequalities, T. Wazewski proved in 1950 the following theorem:

Consider the system of differential inequalities given by $$ \dot{x}_i (t) > f_i(t,x_1, \ldots, x_n), \ i = 1, \ldots, n. $$ If each $f_i$ is non-decreasing with respect to the arguments $x_j$ (for all $j \ne i$), the following estimate is valid: $$ x_i(t) > z_i(t)\ \text{for}\ t_0 < t < t_M,\ i = 1, \ldots, n, \tag{A} \label{A} $$ where $z$ is the solution of the differential equation

$$ \dot{z}(t) = f(t,z),\ z(t_0) = x(t_0). $$

(1) Can we drop the assumption that each $f_i$ is non-decreasing? If not, it is possible to construct an explicit counter-example?

(2) If the assumption that each $f_i$ is non-decreasing is not necessary, what are some current results that guarantee that \eqref{A} holds with weaker assumptions on $f$?


In dimension 1 it is true without the ordered condition, assuming that $x$ and $z$ are suitably differentiable.


At $t = t_0$, we have $x(t_0) = z(t_0)$, and $x'(t_0) > z'(t_0)$ by assumption. This implies that $x > z$ on some interval $(t_0, t_m)$ for $t_m$ sufficiently close to $t_0$. Let $T$ be the infimum of all times where $x(t) \leq z(t)$. Then by continuity we have $x(T) = z(T)$ and $x(t) > z(t)$ for all $t\in (t_0,T)$. Since $x$ and $z$ are differentiable, we have that this means $x'(T) - z'(T) \leq 0$, a contradiction.

In dimension 2 or higher there are many counterexamples.

Define $f(x,y)$ to be the following function.

  1. In the first quadrant, $f(x,y) = (0,0)$ if $x < 1$ and $(0, 1-x)$ if $x \geq 1$.
  2. In the second quadrant, $f(x,y) = (0,0)$.
  3. In the third quadrant, $f(x,y) = (0,0)$ if $y > -1$ and $(0,1+y)$ if $y \leq -1$.
  4. In the fourth quadrant, take $f(x,y) = (0,0)$ within the unit circle, and outside the function $\frac{r-1}{r} (y,-x)$ where $r = \sqrt{x^2 + y^2}$.

One can check easily that $f$ is continuous.

Consider the solution to $\dot{z} = f(z)$ with $z(0) = (0,0)$. The solution is trivially $z(t) = z(0)$.

Consider now the curve $\zeta(t)\in \mathbb{R}^2$ described as follows.

  1. $\zeta(t) = (t,t)$ for $t \in [0,9]$. Smoothly join, observing the condition that $\zeta'_1 > 0$ and $\zeta'_2 \geq -1$ to
  2. $\zeta(t) = (t,20-t)$ for $t \in [11,39]$. Smoothly join, observing the condition that $\zeta'_1 > -1/50$ and $\zeta'_2 > -1$ to
  3. $\zeta(t) = ( (40-t)/100 + 40, (t-40)/1000000 - 20)$ for $t\in [40,4041]$.

You can check that $\zeta'(t) > f(\zeta)$ throughout. But $\zeta_2(4041) < z_2(4040) = 0$ and $\zeta_1(4041) < 0 = z(4041)$.

(If you just want one component violated, $t = 21$ will do in the example above; the example can be also made much simpler in this case: for instance

Let $f(x,y) = (-y,x)$. Let $z(0) = \zeta(0) = (0,0)$. Let $z$ solve $z' = f(z)$ and let $\zeta'$ solve $\zeta' = f(z) + (1,1)$. It is pretty simple to show that $\zeta$ enters the second quadrant in finite time.)


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.